Validation of an assessment tool for mental fatigue applied to rotational shift work - Huysamen, Kirsten Christina (Rhodes University, Faculty of Science, Department of Human Kinetics and Ergonomics, 2014)
Mental fatigue has been proven to be highly prominent during shift work, due to long, irregular working hours and disruption of the circadian rhythm. Measuring mental fatigue has been a challenge for many years, where commonly cognitive test tasks are used to assess mental fatigue. Moreover, these test tasks do not isolate where fatigue is occurring during human information processing. The human information processing system consists of four core stages, each of which requires numerous cognitive functions in order to process information. The Human Kinetics and Ergonomics Department at Rhodes University has developed six cognitive test tasks where each isolates a cognitive function: an accommodation test task, a visual detection test task, a reading test task, a memory test task, a tapping test task and a neural control test task. The cognitive functions include: eye accommodation, visual discrimination, visual pattern recognition, memory duration, motor programming and peripheral neural control. General task-related effect can also be examined for each of these cognitive test tasks which include choice reaction time, visual detection, reading performance, short-term memory, motor control and tracking performance. Additionally, a simple reaction time test task has been developed to analyse simple reaction time. This test task does not isolate a cognitive function. One or more parameters can be examined for each cognitive function and task-related effect. The first aim of this study was to validate numerous cognitive test tasks for mental fatigue in a simulated shift work laboratory setting. The second aim was to assess the validated cognitive test tasks in Phase 1 in a field-based rotational shift work setting. Parameters revealing sensitivity to mental fatigue would be validated for mental fatigue applied to rotational shift work and would be inserted into an assessment tool. In the laboratory setting, the seven cognitive test tasks were examined on four different types of shift work regimes. The first regime was a standard eight-hour shift work system, and the other three were non-conventional shift work regimes. Participants (n = 12 per regime) were required to complete one day shift followed by four night shifts, where testing occurred before and after each shift and four times within each shift. The cognitive test tasks revealing sensitivity to fatigue included: visual detection test task, reading test task, memory test task, tapping test task, neural control test task and simple reaction time test task. The testing of Phase 2 was conducted in three different companies, where each performed a different type of rotational shift work. The six cognitive test tasks validated for mental fatigue in Phase 1 were tested before and after work for each shift type within the rotational shift work system adopted by each company. Company A (n = 18) and Company B (n = 24) performed two-shift rotational shift work systems, where the shift length of Company A was 12-hours and the shift length of Company B was irregular hours. Company C (n = 21) performed an eight-hour three-shift rotational shift work system. Nine parameters revealed fatiguing effects and were inserted into the assessment tool, five of which provided information on a specific cognitive function: error rate for visual discrimination, processing time for visual pattern recognition, error rate for visual pattern recognition, impact of rehearsal time on memory recall rate for memory duration and the high-precision condition for motor programming time. The remaining four parameters provided information on general task-related effects: reading speed for reading performance, recall rate for short-term memory, reaction time for motor control and simple reaction time. Therefore, an assessment tool comprising nine parameters was validated for mental fatigue applied to rotational shift work, where five of the parameters were able to isolate exactly where fatigue was occurring during human information processing and the other four parameters were able to assess fatigue occurring throughout the human information processing chain.
Keywords: Mental fatigue; Shift systems; Performance; Motor ability; Memory